FROM FACTS TO TRUTH IN TAX PROCEDURE - Ilić-Popov, Gordana; Popović, Dejan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
Tax assessment which implies the establishment of the individual tax liability of the specific taxpayer precedes tax collection. It presupposes the prior collection of all facts that can contribute to the correct and accurate determination of the taxable base and afterwards the amount of the tax debt. In the modern information age, the possibility of finding out various facts has significantly increased, but they always require verification. The facts must reflect the tax situation of the taxpayer as objectively and completely as possible. However, the demand for equal treatment of taxpayers in the same or similar tax situations is faced with the reality in which Tax Administration carries out a large number of tax procedures every year so a standard of proof in the form of full conviction cannot be achieved. The initial hypothesis of the authors is that the tax authorities should base their tax decisions on all tax relevant facts which enable them to come to the substantive truth in the tax procedure. Objective, credible and comprehensive facts determined by the Tax Administration, as well as collected from taxpayers or third parties prevent discretionary resolution of tax administrative matters and at the same time ensure the effectiveness and economy of the tax procedure. The „path” to establish a tax solution based on the correct application of the material tax law is not always quick and simple, but it is important to arrive at substantive truth through established facts. Achieving the substantive truth must be accompanied by consistent observance of the principles of legality and equality in taxation.